Potencial das leveduras Rhodotorula glutinis e Sporidiobolus Johnsonii no controle biológico de Xanthomonas axonopodis pv. Phaseoli, na promoção do crescimento do feijoeiro e na ativação de rotas metabólicas ligadas à indução de resistência - Carvalho , Jeferson Carlos (2020)
Hereupon research aimed at identifying working mechanisms related to Xanthomonas axonopodis pv. phaseoli restrain by Rhodotorula glutinis and Sporidiobolus johnsonii. Upon identifying a direct action against the pathogen, we evaluated volatile compounds as well as the ones antimicrobials-none volatiles from R. glutinis (isolates AH 14-3 e AH 20-1), S. johnsonii (isolate AH 16-1) over X. axonopodis pv. Phaseoli in vitro growth. In order to evaluate growth promotion on bean plants (IAPAR Tuiuiú) they were leaded under chamber growth conditions. For each isolate it was performed cell suspension (5 g L-1) as well as the respective culture filtrates, having water as control. Also, Analysis on phytohormone levels synthesized by yeasts was performed using HPLC-MS beyond resistance induction through determination of jasmonic acid, methyl jasmonate and salicylic acid concentration using HPLC-PAD technique. Samples were collected after 0, 3, 6, 24, 27 and 30 hours from treatment establishment. Results stand for cell multiplication decrease at 50,9%, 45,7% and 28,3% due to volatile compounds from R. glutinis (AH 14-3), R. glutinis (AH 20-1) and S. johnsonii, respectively. Beyond an increase around 40% on plants height under the influence of culture filtrates from S. johnsonii and over 40% of foliar area extent under R. glutinis (AH 14-3) cells appliance. Concerning to dry matter of the aerial part cell appliance of R. glutinis (AH 14-3), culture filtrates from R. glutinis (AH 14-3) and cell appliance of R. glutinis (AH 20-1) got the best results which were 33,1%, 33,5% and 29,5%, respectively. Root dry matter increase was around 27% for bean plants treated with cells of R. glutinis (AH 14-3). In turn, total dry matter was increased in plants treated under cell suspension of R. glutinis (AH 14-3), culture filtrates from R. glutinis (AH 14-3) and cell suspension of R. glutinis (AH 20-1), reaching 31,8%, 31,3% e 25,4%, respectively. All isolates were able to produce 3-indolacetic acid, 3-indole butyric acid and gibberellin (GA4). Culture filtrate from R. glutinis (AH 20-1), cell suspension of S. johnsonii and culture filtrate from S. Johnsonii displayed jasmonic acid increment of 169,4, 183,1 and 175,9 µg g-1 fresh tissue passed three hours from treatments apply. On the other hand, salicylic acid increase only took place after 30 hours from R. glutinis (AH 14-3) cell suspension at 5,1 µg g-1 fresh tissue concentration. In short, the isolates R. glutinis (AH 14-3), R. glutinis (AH 20-1) and S. johnsonii acted in conformity with antibiosis mechanisms once they produced volatiles substances, induced resistance in bean crop besides phytohormones production and synthesis of auxin and gibberellin. For all these reasons such strains presented an outstanding ability over biological control of X. axonopodis pv. phaseoli.